2D Nanostructures for Optoelectronic and Green Energy Devices - Sohn, Jung-Inn; Pak, Sangyeon (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue "2D Nanostructures for Optoelectronic and Green Energy Devices", we have collected nine high-quality, original research papers and one comprehensive review paper by outstanding scientists and engineers from relevant fields, covering the topics in optical properties and couplings in 2D nanostructures, spectroscopic analysis in atomic scale, 2D transistors, 2D optoelectronics, and 2D energy storage applications. This Special Issue is expected to attract and enrich readers by providing innovative research articles and a review paper in the field of 2D nanostructures.